Gir cows in their breeding tract - MATHUR, A K; KHOSLA, S K (The Indian Journal of Animal Sciences, 2013)
To assess the economic value and the potential of Gir cows under village conditions, various economic characters like season of conception, season of calving, age at various calvings, calving interval, sex ratio of calves bom, laclalionlength, lact, alioll yield, daily milk yield, peak milk yidd and association of peak yield with lactation yield were studied. The study was based on 2 287 cows identified for conception and 1475 cows offered for recording and subsequent registration under Centraillerd Registration Scheme. No animal offered for registration was rejected before test. There was no definite calving season, although majority of cows calved between November and April. Calving interval in different parities was almost the same. The average age at calving was 3.74±0.03, 5.23±0.04, 6.74±0.06 and 8.15±0.13 years from first to  fourth calvings respectively. The calving interval on the basis of records of 1 245 cows where dates of 2 subsequent calvings were available was 434.61 ± 1.02, 483.25±0.83 and 403.15± 1.31 days from first to third calving. Tbe average for all calvings was 443.27±0.9 4 days. The average lactation length was 293.26±0.89, 291.14:1:1.07, 292.86±1.28 and 295.61±1.74 days from first 10 fourth lactation respectively. The average for all the 4 lactations was 292.87±0,58 days. The average lactation yield was 2215.64±17.36, 2195.02:1:18.05, 2200.64±22.36 and 2 128.04±34.31 kg from first to fourth lactation resspectively. The average for all the 4 lactalions was 2 194.90±10.54 kg. The average daily milk yield was 7.56±0.06, 7.54±0.08, 7.51±0.11 and 7.20±0.14 kg from first to fourth lactation respectively. The average was 7,49±0.04 kg for all the 4 lactations. The average peak milkyield was 1 0.47±0.1 0,10.09:1:0.11, 10.12±0.12 and 9.45±0.22 kg from first to fourth lactation, respectively,and 10. 15±0.07 for all the 4 lactations. The association [actor between peak milk yield and lactation yield was 212.12±0.44, 217.52±0.63, 217.76±0.56 and 224.93±0.81 from firs to fourth lactation, respectively, and 216.49±0.31 for all the 4 lactations.